2010
DOI: 10.1021/la103462z
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Sticky Superomniphobic Surfaces on Transparent and Flexible PDMS Substrate

Abstract: Following the achievement of superhydrophobicity which prevents water adhesion on a surface, superomniphobicity extends this high repellency property to a wide range of liquids, including oils, solvents, and other low surface energy liquids. Recent theoretical approaches have yield to specific microstructures design criterion to achieve such surfaces, leading to superomniphobic structured silicon substrate. To transfer this technology on a flexible substrate, we use a polydimethylsiloxane (PDMS) molding proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 33 publications
2
69
0
1
Order By: Relevance
“…(the ratio of the grating width to pitch) of 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, and 0.8 were prepared and tested. Overall, the receding contact line periodically pinned on, slid on, and jumped across microstructures, presenting stick-slip motions consistent with observations from other researchers [8][9][10][11] . However, we were able to obtain far more details about the motion of the receding meniscus that would not have been possible without the 2-D condition and high-speed imaging.…”
Section: Methodssupporting
confidence: 86%
“…(the ratio of the grating width to pitch) of 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, and 0.8 were prepared and tested. Overall, the receding contact line periodically pinned on, slid on, and jumped across microstructures, presenting stick-slip motions consistent with observations from other researchers [8][9][10][11] . However, we were able to obtain far more details about the motion of the receding meniscus that would not have been possible without the 2-D condition and high-speed imaging.…”
Section: Methodssupporting
confidence: 86%
“…In the literature, it was shown that surface topographies with reentrant curvatures or multivalued roughness such as mushroom-like structures or overhangs can produce superoleophobic properties. [5][6][7][8][9][10][11] Here, we show that different surface morphologies can lead to superoleophobic properties but the presence of thin fi bers allow to reach such properties even if the roughness is low ( R a ≈ 0.2 µm) while higher roughness are necessary with spherical particles ( R a ≈ 2 µm).…”
Section: Discussionmentioning
confidence: 92%
“…While the wetting-resistant surfaces developed since the 1960s (7-10) utilized only surface roughness to trap gas with no interest in the apparent contact angles, superhydrophobic surfaces since the late 1990s (1,11,12) combined the roughness with a hydrophobic material to super-repel water, i.e., display a very large apparent contact angle (θ * > 150°) and a very small roll-off angle (θ rolloff < 10°). For low energy liquids such as oils or organic solvents, a roughness with overhanging topology was necessary to make the hydrophobic material superoleophobic (13,14) or so-called omniphobic (15) or superomniphobic (16,17). Despite the use of prefix omni- (6,(15)(16)(17)(18), however, no natural or man-made surface has been reported to repel liquids of extremely low surface tension/energy (i.e., γ < 15 mJ/m 2 ), such as fluorinated solvents, which completely wet existing materials (10,(19)(20)(21).…”
Section: Main Textmentioning
confidence: 99%
“…For low energy liquids such as oils or organic solvents, a roughness with overhanging topology was necessary to make the hydrophobic material superoleophobic (13,14) or so-called omniphobic (15) or superomniphobic (16,17). Despite the use of prefix omni- (6,(15)(16)(17)(18), however, no natural or man-made surface has been reported to repel liquids of extremely low surface tension/energy (i.e., γ < 15 mJ/m 2 ), such as fluorinated solvents, which completely wet existing materials (10,(19)(20)(21). Departing from the prevailing approach of roughening a hydrophobic material, we first propose the material's inherent wettability, depicted by the intrinsic contact angle θ Y , is irrelevant when dealing with a completely wetting liquid (θ Y = 0°).…”
Section: Main Textmentioning
confidence: 99%